Spatial models cannot compensate for sampling designs unstructured relative to isotopic variation: implications for baseline isoscape development in the Mediterranean Sea - Sarah Magozzi; Clive N. Trueman; Matthew R.D. Cobain; Kirsteen M. MacKenzie; Katie St. John Glew; José A. Canseco; Eric Díaz-Delgado; Emanuela Fanelli; Paola Rumolo; Joan E. Cartes; Boris Espinasse; Davide Agnetta; et al. (Progress in Oceanography, 2026)

Climate-driven phenological shifts and biogeographical constraints of the hydrozoan Velella velella in Mediterranean coastal waters - Clémence Epinoux; Soultana Zervoudaki; Maria Protopapa; Katerina Kikaki; Juan Carlos Molinero; Delphine Bonnet (Frontiers in Marine Science, 2026)
The pleustonic hydrozoan Velella velella forms extensive surface swarms worldwide. However, its ecology and biogeography in the Mediterranean Sea remain poorly documented. This study aims to investigate the biogeography and phenology of V. velella in the Mediterranean Sea and assess its spatial distribution, seasonal dynamics, and long-term phenological shifts linked to regional warming, while evaluating the contribution of citizen science to basin-scale monitoring. We compiled the most comprehensive Mediterranean database to date of V. velella (n = 12,015 records, 1841–2024) by integrating scientific literature, citizen science initiatives, social media, and press reports. Temporal, spatial, and environmental patterns between 2009 and 2024 (representing 93% of the data) were analyzed using Bayesian modelling and kernel-based approaches. Sea surface temperature (SST), NAO, and WeMO data were used to characterize the species’ thermal niche and phenological variability. Citizen science accounted for 72% of observations, highlighting its crucial role in documenting widespread but irregular gelatinous plankton events. Occurrence records exhibited a pronounced west–east gradient, with most presences in the Western Mediterranean basin. Seasonal patterns showed a dominant bloom from March to May, with regional variations and occasional secondary peaks in autumn. Bayesian latent peak models revealed an advance of ~32 days in bloom timing between 2009 and 2024 (posterior slope: –2.0 days yr - ¹, 95% CrI: –7.7 to 3.7). This shift was associated with winter SST warming. Bayesian structural equation modelling further revealed a climate-driven cascade linking large-scale atmospheric variability to phenology, with winter NAO influencing bloom timing through its impact on SST (β = –0.073, 95% CrI: –0.20 to 0.02). V. velella thermal niche spanned 13.0–26.7 °C, with an optimum near 14.5 °C, indicating tight coupling between seasonal dynamics and cooler winter-spring temperatures. These findings establish V. velella as a valuable indicator of surface-ocean variability. This study demonstrates the potential of citizen science for identifying biogeographical and phenological responses of pleustonic taxa to climate change.

Integrating zooplankton biomarkers within the European Marine Strategy Framework Directive (MSFD) assessment - MARIA PROTOPAPA; INMA HERRERA; WILHELM HAGEN; ROLF KOPPELMANN; JONNA ENGSTRÖM-ÖST; CATHERINE TSANGARIS; SOULTANA ZERVOUDAKI; LIDIA YEBRA (Mediterranean Marine Science, 2026)
Biomarkers are increasingly recognized as sensitive indicators of physiological and ecological responses in marine organisms, offering new perspectives for monitoring and ecosystem status assessment. Traditional indices of species composition and biomass, though valuable, often fail to capture early sublethal or functional changes in zooplankton communities. To explore the potential of biomarkers as complementary tools for environmental monitoring within the European Marine Strategy Framework Directive (MSFD), the EuroMarine workshop BIOZOO gathered European experts to evaluate the use of enzyme activities, oxidative stress markers, fatty acids, and stable isotopes for zooplankton-based assessments. Participants identified methodological priorities, including protocol standardization, inter-laboratory calibration, and baseline development, to ensure comparability across regions. This synthesis highlights how integrating biochemical and physiological biomarkers into existing monitoring frameworks can improve the detection of ecosystem responses to environmental pressures such as warming, pollution, and eutrophication. Strengthening biomarker applications in European Seas represents a step toward a more functional, harmonized, and responsive approach to pelagic habitats assessment.

Olive fruit and olive oil in Greece: testimonies of its uses trough mythology, legend, history and philosophy - Maria Protopapas-Marneli; Antonia Trichopoulou (International Journal of Gastronomy and Food Science, 2025)

Probing the settlement signals of Amphibalanus amphitrite - Mado Kotsiri; Maria Protopapa; Gesthimani-Myrto Roumelioti; Athena Economou-Amilli; Eleni K. Efthimiadou; Skarlatos G. Dedos (Biofouling, 2018)

Response of the Calanoid Copepod Clausocalanus furcatus, to Atmospheric Deposition Events: Outcomes from a Mesocosm Study - Epaminondas D. Christou; Soultana Zervoudaki; Ma Luz Fernandez De Puelles; Maria Protopapa; Ioanna Varkitzi; Paraskevi Pitta; Tatiana M. Tsagaraki; Barak Herut (Frontiers in Marine Science, 2017)